Distribution and progression of stem bleeding disease of coconut (Cocos nucifera L.) in some areas of the Philippines - Nemesia C. San Juan; Bachiller; Reynaldo G. Abad (International Coconut Community Journal, 2004)
Records of disease occurrence in surveyed provinces show Davao del Sur having the highest disease incidence of stem bleeding caused by Thielaviopsis paradoxa (de Seynes) von Hohnel. Disease incidence in Malayan Yellow Dwarf x West African Tall (MYD x WAT) hybrid at the PCA’s Zamboanga Research Center was relatively lower than the other areas observed. Tall genotypes are less susceptible to the disease as shown in the province of Quezon where the cultivar Laguna Tall is predominantly grown. The incidence of stem bleeding was found to be related with palms age. More incidence of the disease was noted in palms between 11-15 years old. Study on the spatial distribution of the disease from l991 to l995 show that the disease initially occurred in random foci, and, subsequently infected adjacent palms. The disease progress curves suggest that stem bleeding follows a sigmoid curve. It follows that the progress of the disease at any given time is a function of the initial inoculums and the number of effective contact points between susceptible host and inoculums per unit time. Analysis of the infection rates using logistic growth model showed that the rate of disease increase ranged from 0.029 to 0.218 per unit per year and 0.227 per unit per year in all the six experimental areas. Increase in disease incidence is directly related to high amount of rainfall.